Analysis Of Infrastructure Usage Among Students In Adopting Education 4.0 At Higher Learning Institution In Johor - YUSOFF, MOHD ZARIR (Research in Management of Technology and Business, 2023)
Nowadays Education 4.0 promotes education in a novel way, primarily using technology-based tools and resources. However, education in Malaysia still lacks exposure in terms of IoT to students and educators. Therefore, this study aims to determine the level of infrastructures usage among students in adopting education 4.0. It’s also aims to determine the level performance in adopting education 4.0 among students and to determine the relationship between infrastructures usage in adopting education 4.0 and performance in adopting education 4.0 among students was be focused on University Tun Hussein Onn Malaysia and University Technology Malaysia. The data obtained was analyzed descriptively and correlated using Statistical Package for Science (SPSS) and Microsoft Excel. This research used an online survey questionnaire like a google form to collect the data from 351 valid respondents. The results show that the level of infrastructures usage influences performance in adopting education 4.0 among students in UTHM and UTM but because of that if level of infrastructure usage had a is increase and level performance among student in adopting education 4.0 increase, so the relationship between them is positive.